Implementasi Additive Ratio Assesment (Aras) Program Keluarga Harapan (PKH) Lansia dalam Meningkatkan Kesejahteraan Masyarakat Desa Pasar Kerkap Perspektif Ekonomi Islam - Indri Febrianti; Khairiah Elwardah; Eeng Juli Efrianto (Economic Reviews Journal, 2025)
Poverty is a complex issue that requires comprehensive strategies to address, including through the Family Hope Program (PKH), which provides cash assistance to poor households under certain conditions. This study aims to analyze the effectiveness of PKH in improving the welfare of the elderly in Pasar Kerkap Village using the Additive Ratio Assessment (ARAS) method. This method allows for a more systematic evaluation of the program's impact, particularly in the context of Islamic economics. The results indicate that the implementation of ARAS in PKH has improved the targeting of social assistance, although challenges remain in fund disbursement and community understanding. This study provides recommendations to enhance program transparency and socialization, as well as strengthen collaboration between the government and the community to ensure a more effective and sustainable program.